Hubungan Kecepatan Kendaraan dengan Derajat Kejenuhan - Erwin Kusnandar (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
On street parking at this time can not be avoid yet, on the other hand the existence of parking will affect traffic performance, how far the trouble can be happened. With apparatus of analysis operational traffic performance can be determined using some performance variable like speed, volume, and capacities. Intention of this research is to look for relationship between speeds of vehicle with degree of saturation. This relationship can benefit to all planner in specifying location criterion traffic performance that happened can be estimated by configuration form of on street parking. However, a further research still need a continuation development, mainly concerning with road type and amount of samples. Especially the result of this research can produce an alternative approach for planning an on street parking.